Effect of pecuniary costs and time costs on choice of healthcare providers among caregivers of febrile children in rural Papua New Guinea - Takahiro Tsukahara; Takuma Sugahara; Seiritsu Ogura; Francis Wanak Hombhanje (Health Economics Review, 2019)
Background: User fees, transportation costs, and time costs impair access to healthcare by rural communities in low and middle income countries. However, effects of time costs on demand for healthcare are less understood than effects of user fees for health providers. In addition, prospective patients might not know about all health services available. This study aims to investigate how the family caregivers of febrile children respond to the pecuniary costs and time costs in their choice of health providers in rural Papua New Guinea. Methods: Using an original questionnaire, we surveyed households in the catchment area surrounding Dagua Health Center in East Sepik Province, Papua New Guinea, during February-March 2015. We estimated the probability of choosing one among four categories of providers (i.e., the health center, aid posts, village health volunteers [VHVs], or home-treatment) via a mixed logit model in which we restrict alternatives to those for which family caregivers knew cost information. Results: Of 1173 family caregivers, 96% sought treatment for febrile children from four categories of providers. Almost all knew the location of the health center and a health volunteer, but only 50% knew the location of aid posts. Analysis by discrete choice model showed that pecuniary costs and time costs were inversely associated with the probability of choosing any type of provider. We then changed pecuniary costs and time costs counterfactually to calculate and compare the probability of choosing each provider. Time costs affected the choice more than pecuniary costs, and individual heterogeneity appeared among caregivers with respect to pecuniary costs. When pecuniary or time costs of VHVs are altered, substitution between VHVs and home-treatment appeared. Conclusions: Our findings suggest that policies to increase awareness of aid posts and reduce time costs in addition to treatment fees for each category of healthcare provider could help developing economies to improve access to essential healthcare services.
Keywords: 330; Health demand; Community health worker; Time costs; Choice set formation; Mixed logit; Oceania; Pacific